2023
DOI: 10.3390/jcm12082904
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Donors Right Hepatectomy versus Open Donors Right Hepatectomy: A Meta-Analysis

Abstract: Background: How to obtain a donor liver remains an open issue, especially in the choice of minimally invasive donors right hepatectomy versus open donors right hepatectomy (MIDRH versus ODRH). We conducted a meta-analysis to clarify this question. Methods: A meta-analysis was performed in PubMed, Web of Science, EMBASE, Cochrane Central Register, and ClinicalTrials.gov databases. Baseline characteristics and perioperative outcomes were analyzed. Results: A total of 24 retrospective studies were identified. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Advantages shown by minimally invasive donation are lower blood loss, shorter hospitalization and lower overall complication rate, but increased operation time [26]. In contrast, previous work has described an increased rate of biliary complications in both donor and recipient, but this was not replicated in a recent meta-analysis [26,27]. The benefits described also apply to robotic donor surgery with less evidence [28].…”
Section: Discussionmentioning
confidence: 99%
“…Advantages shown by minimally invasive donation are lower blood loss, shorter hospitalization and lower overall complication rate, but increased operation time [26]. In contrast, previous work has described an increased rate of biliary complications in both donor and recipient, but this was not replicated in a recent meta-analysis [26,27]. The benefits described also apply to robotic donor surgery with less evidence [28].…”
Section: Discussionmentioning
confidence: 99%
“…To ensure donor safety after liver surgery, it is necessary to secure a certain RLV. It is well known that leaving a RLV of 30% or more can ensure operative safety in the current practice [5]. One study reported that the operation of living donors with a RTVR < 30% could be safely performed if we carefully selected the candidates [6].…”
Section: Discussionmentioning
confidence: 99%
“…Liver size is a critical factor for the selection of living donors in LDLT. Currently, the right hemiliver is mainly used as a graft to meet the demand for an adequate liver volume in adult recipients [5]. The residual liver volume (RLV) of living donors is much smaller after right liver donation, which would also be insufficient to prevent postoperative hepatic failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation